2017
DOI: 10.1093/mutage/gex032
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Pig-a mutations in T lymphocytes of rats treated with procarbazine

Abstract: Procarbazine is a primary component of antineoplastic combination chemotherapy often used for the treatment of Hodgkin's lymphoma. It is believed that cytostatic and cytotoxic properties of procarbazine are mediated via its interaction with genomic DNA. Procarbazine is a carcinogen in animal models; it is classified as Group 2A compound by IARC. Also it is known as an in vitro and in vivo mutagen and genotoxicant. However, the molecular mechanism by which procarbazine induces mutations is not thoroughly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
3
23
1
Order By: Relevance
“…ENU induced T>A mutations consistent with alkylation of thymine, specifically O 2 -and O 4 -ethyl thymine 50, 51 . We found that PRC induced T>A mutations and, to a lesser extent T>C mutations, which is consistent with the pattern of mutations that was observed in an endogenous gene 52 . The mutation spectrum of TEM was significantly different from controls, but there were no significant changes in specific SNV types.…”
Section: Resultssupporting
confidence: 89%
“…ENU induced T>A mutations consistent with alkylation of thymine, specifically O 2 -and O 4 -ethyl thymine 50, 51 . We found that PRC induced T>A mutations and, to a lesser extent T>C mutations, which is consistent with the pattern of mutations that was observed in an endogenous gene 52 . The mutation spectrum of TEM was significantly different from controls, but there were no significant changes in specific SNV types.…”
Section: Resultssupporting
confidence: 89%
“…Likewise, the maximal increases in mean RBC CD59− frequencies were~105.9-fold and~374.4-fold over background in the 3-day and 28-day studies, respectively. The strong Pig-a responses described herein for PCZ in the 3-day study are greater than earlier positive Pig-a findings for similar treatments in CD-1 mice treated orally with 37.5-150 mg/kg/day PCZ (Phonethepswath et al, 2013) and in Sprague-Dawley rats exposed intraperitoneally to 100 mg/kg/day PCZ (Revollo et al, 2017).…”
Section: Procarbazine Hydrochloridecontrasting
confidence: 77%
“…Although the two test chemicals in our study, PCZ and EC, have been investigated previously in similar integrated studies as well as assays measuring single genotoxicity endpoints, including Pig‐a gene mutation (Phonethepswath et al, ; Bemis et al, ; Labash et al, ; Stankowski et al, ; Pu et al, ; Revollo et al, ), the data reported herein allow comparisons between the responses for multiple genotoxicity endpoints as a function of two commonly employed treatment regimens (short‐term, 3‐day and subchronic, 28‐day studies). In addition to conducting multiple genotoxicity assays, analyses were made to collect data for hematology, clinical chemistry, organ weight, and other general toxicity indicators.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…While the magnetic enrichment did not eliminate all CD48 + BMGs, it made the population of CD48‐deficient BMGs more prominent, as can be seen in Figure D. Mutant BMGs (from the “CD11B‐mutants” gate) from Rats #15, 16, 19, and 20 were sorted in small pools of 25 cells per well for sequencing of the Pig‐a gene using a previously described protocol, Mutation Analysis with Multiplexed Libraries (MAML; Revollo et al, , ). Wild‐type BMGs (from the gate “WT‐granulocytes” in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Miura et al (, ) found that the average mutant frequency of proaerolysin‐resistant T‐cells isolated from rat spleens was 2.3 × 10 −6 . Previous studies demonstrated that the spontaneous mutant frequency of CD48‐deficient Pig‐a mutant T‐cells in rats was 3.5 ± 2 × 10 −6 and 10.5 ± 5.5 × 10 −6 (Dobrovolsky et al, ; Revollo et al, ). For in vitro Pig‐a assays, the background frequency of Pig‐a mutants was 20–30 × 10 −6 for L5178Y Tk +/− cells (Wang et al, ) and 0.76 × 10 −6 for TK6 cells (Kruger et al, ).…”
Section: Discussionmentioning
confidence: 96%